2010
DOI: 10.1111/j.1398-9995.2009.02121.x
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life of food allergic patients: comparison with the general population and other diseases

Abstract: HRQL is impaired in food allergic adolescents and adults, compared to the general population, and it is intermediate in magnitude between DM and RA, asthma and IBS. Children show the least impact on generic HRQL from food allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
170
2
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(184 citation statements)
references
References 32 publications
(38 reference statements)
6
170
2
6
Order By: Relevance
“…Individuals with food allergy have been found to have poorer HRQL than the general population and individuals with diabetes, but better HRQL than patients with rheumatic arthritis, asthma or irritable bowel syndrome [10]. Although validated instruments were not used, it was shown that children with peanut allergy reported more impact on HRQL and more fear than children with insulin-dependent diabetes [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with food allergy have been found to have poorer HRQL than the general population and individuals with diabetes, but better HRQL than patients with rheumatic arthritis, asthma or irritable bowel syndrome [10]. Although validated instruments were not used, it was shown that children with peanut allergy reported more impact on HRQL and more fear than children with insulin-dependent diabetes [9].…”
Section: Discussionmentioning
confidence: 99%
“…Several instruments have been developed and validated for measuring HRQL in all ages and show that food allergy has a high psychosocial impact on children, adolescents, adults and their families [3][4][5][6][7][8][9][10]. In most studies where parents have reported HRQL on their child's behalf, typically only the mother has participated in the research.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown that FA has a negative impact on an individual's HRQL [3,4,5]. Within the framework of the EuroPrevall project, an FA-specific quality of life questionnaire for adults has been developed and validated, which was used in this study [8,12].…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation is a difference in health-related quality of life (HRQL). Various studies have shown that FA has a negative impact on an individual's HRQL [3,4,5]. A more impaired HRQL could be a reason to seek medical care, irrespective of the severity of symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…dustrie über beruflich bedingte Atemwegsbeschwerden berichtet, die mit einer Sensibilisierung auf die Speicherproteine Gly m 5 und Gly m 6 in Verbindung gebracht wurden [14]. Solche Atemwegsbeschwerden wurden zuvor nur im Zusammenhang mit einer Sensibilisierung auf Gly m 1 und Gly m 2 beobachtet [3].…”
Section: Allergene In Soja(produkten)unclassified